Mixed mode cation exchange chromatography ligands based on 1,3-dioxoisoindolin-2-yl structures - Liao, Jiali; Belisle, Christopher; Lozano, Edwin (2023)
The subject invention pertains to proteins are purified by a mixed-mode chromatography system formed by attaching a ligand with cation exchange and hydrophobic 1,3-dioxoisoindolin-2-yl group functionalities to a large-pore support matrix, the only linkage between the ligand and the support matrix being a chain having a backbone of one, two, three, four, or five atoms between the hydrophobic group and the support matrix.